Gambaran Intelligence Quotient (IQ) Di MTs N 1 Karanganyar - Sri Hartini; Anniez Rachmawati Musslifah (Concept: Journal of Social Humanities and Education, 2024)
Individuals have important factors that influence them. Intelligence is the term referred to by scientists. Intelligence can be said to be an individual's ability, dexterity, shrewdness and ingenuity. Individuals compete to become intelligent humans, because only with intelligence can individuals become successful. Intelligence Quotient (IQ) or commonly called intellectual intelligence, is an individual's ability to think that is innate from birth which allows individuals to act in a certain way, as well as an ability that can be measured in a test. This research method is a correlational quantitative approach. The population of this research is all prospective students of class VII MTS N 1 Karanganyar, Gondangrejo for the 2025/2025 academic year in 7 rooms totaling 164 students. The research sample was prospective class VII students at MTs N 1 Karanganyar, totaling 110 students. The data collection method was carried out using psychological test tools, namely TIKI-M (Indonesian Collective Intelligence Test) and documentary. The data analysis used is descriptive analysis. Based on the results of data analysis and research discussion, it can be concluded that the mean level of intelligence quotient (IQ) of MTS N 1 Karanganyar prospective students for the 2024/2025 academic year is 107, which is included in the average category. Based on the frequency distribution of intellectual intelligence, it can be seen that the level of intellectual intelligence of MTS N 1 Karanganyar prospective students is 68.18% at the average level, 27.27% is at the above average level, and as much as 4.54% is at a superior level.